2023
DOI: 10.1021/acsomega.2c05971
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Visible-Light-Induced Photocatalytic Activity in M(III)Salophen-Decorated TiO2 Nanoparticles for Heterogeneous Degradation of Organic Dyes

Abstract: In this work, the construction of two heterojunction photocatalysts by coordinative anchoring of M(salophen)Cl complexes (M = Fe(III) and Mn(III)) to rutile TiO 2 through a silica−aminopyridine linker (SAPy) promotes the visible-light-assisted photodegradation of organic dyes. The degradation efficiency of both cationic rhodamine B (RhB) and anionic methyl orange (MO) dyes by Fe− and Mn−TiO 2 -based catalysts in the presence of H 2 O 2 under sunlight and low-wattage visible bulbs (12−18 W) is investigated. Ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Furthermore, TiO 2 is considered harmless to the environment. , ZnO is another semiconductor commonly implemented in heterogeneous photocatalytic systems. , Both of them (TiO 2 and ZnO) are photocatalytically active only under UV irradiation due to their high band gap value. Various strategies have been implemented to improve photocatalytic activity (e.g., doping, , sensitization, , quantum dots, , heterostructures with other semiconductors with smaller band gap, , and anion vacancies). The heterostructures have the advantage that can improve the photocatalytic activity and reduce the charge recombination rates. , Also, Rajkumar et al reported that ZnO nanoparticles show activity against Bacillus sp., Escherichia coli, Staphylococcus aureus, Vibrio cholerae, Corynebacterum sp., and Salmonella sp., and the bacterial deactivation was associated with destruction of cellular walls by actions of the reactive oxygen spices (ROS) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TiO 2 is considered harmless to the environment. , ZnO is another semiconductor commonly implemented in heterogeneous photocatalytic systems. , Both of them (TiO 2 and ZnO) are photocatalytically active only under UV irradiation due to their high band gap value. Various strategies have been implemented to improve photocatalytic activity (e.g., doping, , sensitization, , quantum dots, , heterostructures with other semiconductors with smaller band gap, , and anion vacancies). The heterostructures have the advantage that can improve the photocatalytic activity and reduce the charge recombination rates. , Also, Rajkumar et al reported that ZnO nanoparticles show activity against Bacillus sp., Escherichia coli, Staphylococcus aureus, Vibrio cholerae, Corynebacterum sp., and Salmonella sp., and the bacterial deactivation was associated with destruction of cellular walls by actions of the reactive oxygen spices (ROS) .…”
Section: Introductionmentioning
confidence: 99%
“… 24 , 25 Both of them (TiO 2 and ZnO) are photocatalytically active only under UV irradiation due to their high band gap value. Various strategies have been implemented to improve photocatalytic activity (e.g., doping, 26 , 27 sensitization, 28 , 29 quantum dots, 30 , 31 heterostructures with other semiconductors with smaller band gap, 32 , 33 and anion vacancies 34 ). The heterostructures have the advantage that can improve the photocatalytic activity and reduce the charge recombination rates.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Pesticides, dyes, medicines, and even persistent organic pollutants have all been demonstrated to be eliminated successfully through the use of photocatalytic technologies. [4][5][6][7] Also, compared to other forms of treatment, photocatalytic technology has several benefits. A lowcost method is one that does not involve the use of chemicals or the creation of dangerous byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Dye pollution is one of the most pressing issues facing the industry. In fact, much of the synthetic dye does not stick, is lost in wastewater associated with manufacturing, and is usually discarded without treatment [1,2]. Organic dyes are one of the leading factors of pollutants in the water, which is generated by the wastewater discharges of several manufacturing sectors including textiles, plastics, dyeing, photography, printing, and tanning [3].…”
Section: Introductionmentioning
confidence: 99%